Entrepreneurship Opportunities of Food Duck Cull Base Product for Small Scale Duck Farmers in Oesapa Kupang City - Lole, Ulrikus Romsen; Mulyantini S S, Ni Gusti Ayu; Suryatni, Ni Putu Febri; Suryani, Ni Nengah (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: The aim of this community service program is to increase entrepreneurship knowledge and skills in making a variety of food products from duck eggs and duck meat from ducks that are no longer productive. Method: The activity method is providing training about entrepreneurship, and demonstrations of processing ducks into various ready-to-eat food products. Participant consisted of 15 duck farmers from Oesapa Kupang city. Practical Application: Processing cull or rejected duck meat provides the right solution for farmers to overcome the problem of handling ducks that are not productive and can also improve family income and increase consumption of animal protein for the community. Conclusion: Small scale duck farmers were able to increase their knowledge about entrepreneurship and improve skills in making a variety of nutritious food made from duck eggs and duck meat.